The role of CXCL16 in atherosclerosis: from mechanisms to therapy - Liu, Yue; Tian, Xintao; Jia, Chunyan; Cheng, Xinrui; Cui, Changxing; Li, Cuiping; Yang, Shaonan (Frontiers in Immunology, 2025)
Atherosclerosis (AS), as the primary pathological basis of cardiovascular and cerebrovascular diseases, is closely associated with chemokines in its occurrence and progression. CXCL16 establishes a new link between chemokines and AS. We briefly introduced the structural characteristics of CXCL16 and its specific receptor CXCR6, as well as related signaling pathways. Furthermore, the significant role of CXCL16 in the progression of AS was elaborated from the perspective of pathological mechanisms and signal pathways. Meanwhile, we objectively evaluated the potential arterial protective effects of CXCL16. Finally, we discussed various novel therapeutic strategies to alleviate AS by targeting the inhibition of CXCL16 and its regulatory pathways. This review systematically summarizes the multifaceted roles of CXCL16 in AS, providing theoretical foundations and research insights for the precise prevention and treatment of AS.